Antifungal activity of Verbenaceae and Labiatae families essential oils (2012)
ABSTRACT: Plant derivates as essential oils and extracts have shown important antifungal activity. Fusarium oxysporum is an important emergent fungus causing opportunistic infections as fungemia with high mortality rates. Also is known as onychomycosis agent. Currently, there are limited options for treatment of this fungus due to its relative resistance to most antifungal agents. In addition, Trichophyton rubrum and T. mentagrophytes are the most common etiologic agents of superficial fungal infection known as dermatophytosis that affects skin, hair and nails. These mycoses, although normally not are lethal, represent a cosmetic problem unpleasant with difficult to be cured, causing considerable financial losses. In this study, the antifungal activity of seventeen essential oils and three extracts belonging to the families Verbenaceae and Labiatae, was evaluate against this fungus according to the Clinical and Laboratory Standards Institute (CLSI-M38A). The MIC (Minimal Inhibitory Concentrations) was defined as the lowest essential oil and extract dilution that resulted in 80% of inhibition of visible growth after 48 h of incubation for F. oxysporum and after six days for dermatophytes. Also, the cytotoxicity assay for 18 samples was carried out using tetrazolium-dye MTT technique. IC50 and selective index values were calculated. The compositions and compounds quantification chemical of the most potent antifungal oils were determinate using GC-MS and GC-FID analysis, respectively. The results showed strong activity among 70% at 80% of samples evaluated against dermatophytes and from 20% against F. oxysporum. The lowest MIC values were obtained with citral chemotype Lippia alba oil (BC2) at concentrations of 31.25 and 125 µg/mL on T. rubrum and T. mentagrophytes, respectively, but not against F. oxysporum. Moreover, the oil from Minthostachys mollis (Kunth) Griseb (MEO2) showed strong activity against all fungi evaluated. Active samples against dermatophytes and F. oxysporum were not cytotoxic on Vero cells ATCC CCL-81; excluding Lippia origanoides Kunth (5E), carvone chemotype Lippia alba (TS) and Mintostachys mollis oil (MEO2). The essential oils with the highest selectivity index (SI) values were Aloysia triphylla (AEO1) and L. alba oil (BC2) on dermatophytes. The main component of most active L. alba oils was characterized by carvone (TS, CC1) and citral (BC2). To L. origanoides oils was found carvacrol (1A, 5E) and thymol (6F) as main component. Pulegone and cis-piperitone epoxide were the main constituents of Minthostachys mollis MEO1 and MEO2 oils, respectively. The presence of these main components in essential oils may be the responsible of the antifungal activity. These findings is very important because confirm the potential of essential oils as a source of new anti-dermatophytes.